2023
DOI: 10.1002/adfm.202212566
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel‐Based Artificial Mucosa Restores Local Immune and Microbial Homeostasis for Treating Ulcerative Colitis

Abstract: Ulcerative colitis (UC) is a common inflammatory bowel disease driven by the dyshomeostasis of intestinal immune system and microbiota, but its treatment options are limited due to impaired epithelial barrier integrity and function. Herein, a multifunctional biomimetic hydrogel is developed as artificial colonic mucosa, which can readily establish a bioadhesive barrier at the ulcer site and restore local immune and microbial homeostasis to exert potent anti-inflammatory effect. The hydrogel framework is genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…38 The disease activity index (DAI) measures treatment efficacy by examining fecal characteristics, occult blood levels, and weight reduction. 39 The PBS group exhibited red, watery feces, whereas the healthy and TMNR groups exhibited a clean anus instead (Figure S17). The TMNR group exhibits a protective effect on colitis-induced body weight loss (Figure 5b), a lower DAI value (0.52, Figure 5c), and a longer colon length (Figure 5d-e) than the other three groups, showing that the mice were significantly protected against DSS-induced colitis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The disease activity index (DAI) measures treatment efficacy by examining fecal characteristics, occult blood levels, and weight reduction. 39 The PBS group exhibited red, watery feces, whereas the healthy and TMNR groups exhibited a clean anus instead (Figure S17). The TMNR group exhibits a protective effect on colitis-induced body weight loss (Figure 5b), a lower DAI value (0.52, Figure 5c), and a longer colon length (Figure 5d-e) than the other three groups, showing that the mice were significantly protected against DSS-induced colitis.…”
Section: Resultsmentioning
confidence: 99%
“…Weight loss is essential for monitoring the course of IBD in mice caused by DSS . The disease activity index (DAI) measures treatment efficacy by examining fecal characteristics, occult blood levels, and weight reduction . The PBS group exhibited red, watery feces, whereas the healthy and TMNR groups exhibited a clean anus instead (Figure S17).…”
Section: Resultsmentioning
confidence: 99%
“…105 A hydrogel loaded with growth factors was formulated by the simple mixing of clinically tested precursors, including fibrinogen, thrombin, dopamine/ thiol dual-modified hyaluronic acid (HA-SH-DA), Ag, basic fibroblast growth factor (bFGF) and alanyl-glutamine (ALG). 106 Moreover, both bFGF and ALG are approved wound treatments that can be stably delivered to the site of intestinal injury through hydrogel-based DDSs for accelerating healing of ulcerative mucosa (Fig. 3C).…”
Section: Growth Factorsmentioning
confidence: 99%
“…7A and B, a hydrogel containing bFGF and ALG was found to stimulate cell proliferation and promote epithelial cell migration leading to faster re-epithelialization of damaged tissue resulting in ulcer healing. 106 The efficacy of topical application of SAPH was assessed using endoscopy on TNBS-induced ulcers where it was observed that SAPH treatment significantly promoted wound healing compared to carrier treatment on day 0 110 (Fig. 7C).…”
Section: Applications Of Hydrogel-based Ddss In Ibd Treatmentmentioning
confidence: 99%
“…[8] By far, a number of nanoparticles (NPs), engineered bacteria, polymers, biomolecules, and organic molecules have been developed as potent mimic enzymes that exhibit catalase (CAT) or superoxide dismutase (SOD) activity, which can deplete excessive ROS. [9][10][11][12] In the biomedical field, nanomaterials can overcome the disadvantages of natural antioxidants such as short cycle time, increased toxic side effects from multiple dosing, and low absorption rate and bioavailability. [13] Among them, noble metal NPs have attracted great interest due to their high stability, mass production, and tunable catalytic properties.…”
Section: Introductionmentioning
confidence: 99%